THE ROLE OF THE DIGITAL ECONOMY IN MODELING THE FINANCIAL ACTIVITIES OF ENTERPRISES - Yuldosheva, Gulnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article examines the profound role the digital economy plays in modeling the financial activities of enterprises. It delves into the modern tools and mechanisms for implementing efficient financial processes and facilitating digital transformation in companies. The study harnesses a qualitative methodological approach and provides an empirical analysis of the digital economy's impact on enterprise finance, illustrating how the adoption of digital technology reshapes financial practices.